Effects of social factors on the COVID-19 cases and its evolution in Hubei, China - Yin, Shuqi; Du, Lijing; Meng, Dongmei (Frontiers in Public Health, 2023)
Social factors could affect the evolution of epidemics. The COVID-19 in Hubei province of China was taken as an example to investigate the impact of social factors including the resident population, universities, hospitals, the distance between Wuhan seafood market and 17 cities in Hubei Province, and distribution of medical materials on COVID-19. We found that the cities could be divided into three groups grounded on the number of confirmed cases and the time course data of cases. Through linear regression analysis, it was verified that these factors had a great impact on the number of confirmed cases and evolution of COVID-19. With the increase in the number of universities, the number of confirmed cases and the number of new cases raised significantly. With an increment in population density, the number of new cases multiplied evidently. In addition, the farther away from the Wuhan seafood market, the fewer confirmed cases. It was worth noting that the insufficient increase of medical supplies in some cities still led to a significant increase in new cases. This kind of influence was regional, and their lag periods were also different. Through comparison with Guangdong Province, it was concluded that social factors will affect COVID-19. In general, the study found that it was very important to promote the construction of medical schools and do a good job in the rational distribution of medical materials, which could effectively help policy-making.